Duração do teste de germinação do capim-tanzânia - Tomaz, Camila de Aquino [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
O tempo de 28 dias recomendado pelas Regras para Análise de Sementes (RAS) para o teste de germinação de sementes de Panicum maximum é considerado excessivo para produtores, comerciantes e laboratórios de análise de sementes forrageiras, que dependem dos resultados do teste para a tomada de decisões de controle de qualidade e comercialização. Desta forma, o presente trabalho teve o objetivo de determinar o tempo necessário para a condução do teste de germinação de Panicum maximun cv. Tanzânia. Na pesquisa, 30 lotes de sementes fiscalizadas foram submetidas ou não (testemunha) aos seguintes tratamentos para a superação dormência: germinação em substrato umedecido com KNO3 (0,2%), escarificação com ácido sulfúrico (98% 36N) por 5 minutos e testemunha. Os lotes foram avaliados pelo teste de germinação sob duas condições de temperaturas alternadas (20-30ºC e 15-35ºC), com luz (78 μmol s-1 m-2/ 8h). Para a identificação da data de término do teste foram realizadas contagens diárias do número de plântulas normais e para cada lote, tratamento de superação de dormência e temperatura, foi ajustada uma curva de crescimento para a avaliação da germinação. As sementes remanescentes do teste de germinação foram seccionadas longitudinalmente e medianamente através do embrião para a realização do teste de tetrazólio. As duas metades da semente foram imersas em uma solução de tetrazólio a 0,1% e mantidas em câmara escura, à 37ºC, por um período de 3 horas e após esse período as sementes foram lavadas e a leitura feita imediatamente, classificando-se as sementes em viáveis e não viáveis (mortas). No delineamento experimental os 30 lotes foram considerados...

The time of 28 days recommended by the Rules for Seed Analysis (RAS) to test the germination of Panicum maximum is considered excessive for producers, traders and laboratory analysis of forage seeds, which depend on the results of the test for making decisions of quality control and marketing. The present study aimed to determine the time required for the conduct of the germination test of Panicum maximum cv. Tanzania. In the survey, 30 seed lots were audited or not (control) to the following treatments to overcome dormancy: germination in soak with KNO3 (0.2%), scarification with sulfuric acid (98% 36N) for 5 minutes and witness. The lots were assessed by the germination test under two conditions of alternating temperatures (20-30ºC and 15-35°C) with light (78 μmol s-1 m-2/ 8h). To identify the date of termination of the test were made daily counts of the number of normal seedlings for each lot, treatment of overcoming dormancy and temperature, was fitted a curve of growth for the assessment of germination. The remaining seeds in the germination test were sectioned longitudinally through the embryo and medium for the completion of the tetrazolium test. The two halves of the seeds were immersed in a solution of tetrazolium to 0.1% and kept in dark room, at 37º C for a period of 3 hours and after that period the seeds were washed and reading made immediately, sorting out the seeds into viable and non viable (dead). In the experimental design the 30 lots were considered the repetitions, resulting in estimates of the parameters of the segmented regression model for each treatment, was performed an analysis of variance where the treatments were compared to overcome dormancy and temperature. Through regression model was targeted to estimate the time required to conduct the germination test, determining whether the value at which the difference between the estimated asymptote... (Complete abstract click electronic access below)
Keywords: Germinação; Sementes; Capim-tanzania; Panicum maximum; Seed; Germination test; Dormancy breaking treatments; Alternating temperatures